Housing system and herd size interactions in Norwegian dairy herds; associations with performance and disease incidence - Simensen, Egil (BioMed Central, 2010)
BACKGROUND: According to the Norwegian animal welfare regulations, it has been forbidden to build new tie-stall barns since the end of 2004. Previous studies have shown that cow performance and health differ between housing systems. The interaction between housing system and herd size with respect to performance and disease incidence has not been evaluated. METHODS: Cow performance and health in 620 herds housed in free-stall barns were compared with in 192 herds housed in tie-stall barns based on a mail survey and data from the Norwegian Dairy Herd Recording and Cattle Health Systems. The housing systems herds were comparable with respect to herd size (15-55 cows). Associations between performance/disease incidence and housing system, herd size and year of building the cow barn were tested in general linear models, and values for fixed herd size of 20 and 50 cows were calculated. On the individual cow level mixed models were run to test the effect of among others housing system and herd size on test-day milk yield, and to evaluate lactation curves in different parities. All cows were of the Norwegian Red Breed. RESULTS: Average milk production per cow-year was 134 kg lower in free-stall herd than in tie-stall herds, but in the range 27-45 cows there was no significant difference in yields between the herd categories. In herds with less than 27 cows there were increasingly lower yields in free-stalls, particularly in first parity, whereas the yields were increasingly higher in free-stalls with more than 45 cows. In free-stalls fertility was better, calving interval shorter, and the incidence rate of teat injuries, ketosis, indigestions, anoestrus and cystic ovaries was lower than in tie-stalls. All of these factors were more favourable in estimated 50-cow herds as compared to 20-cow herds. In the larger herd category, bulk milk somatic cell counts were higher, and the incidence rate of mastitis (all cases) and all diseases was lower. CONCLUSION: This study has shown that there is an interaction between housing system and herd size, and that performance and health is not universally better in small free-stalls than in tie-stalls.